Time to Shuffle the Deck: Recommendations to Improve Gender Representation at Gambling Studies Conferences - Monson, Eva; Arsenault, Nicole; Savard, Annie-Claude; Morvannou, Adèle; Baxter, Carling M.; Hahmann, Tara; Hitch, Catherine; Kesaite, Viktorija; Palmer du Preez, Katie; Légaré, Andrée-Anne (Critical Gambling Studies, 2024)
The underrepresentation of women speakers at academic conferences in the gambling studies field is historic and pervasive yet the pressing issue of gender disparity in the field has yet to be adequately acknowledged or addressed. In 2023, an International Forum, hosted by Research And Networking for Gambling Early-career Scholars (RANGES) brought together ten early career researchers in the gambling studies field, all women, from varied research environments and disciplinary backgrounds. The International Forum aimed to answer the question: How can gambling studies conferences improve gender representation and become more inclusive and equitable? The result is this commentary which constitutes a set of recommendations related to gambling studies conferences designed to be implemented broadly as a form of collective action that will (1) contribute to the development of a shared understanding and awareness of the pressing issue of gender disparity; (2) provide actionable pathways for change; and (3) trigger a systemic and comprehensive change in the face of ongoing gender disparity with the goal of creating a more equitable, diverse and inclusive research field.